MEASUREMENT OF THE REGRESSION RATE IN A HYBRID ROCKET MOTOR BY ACQUIRING THE HELMHOLTZ FREQUENCY IN THE COMBUSTION CHAMBER - Matos, I. P. B.; Silva, R. M.; Pimont, L. J.; Lacava, P. T. (Revista de Engenharia Térmica, 2022)
Low thrust values obtained with a hybrid rocket motor (HRM) are a consequence of the difficulty in quickly mixing the fuel and oxidizer, which is characterized by a low regression rate of the fuel grain. Therefore, the measurement of this parameter is of great importance in studies that aim at solutions for this deficiency in HRM. Several studies calculate a reliable value of the average regression rate over time by measuring the total mass of fuel before and after each burn. A method to measure instantaneous regression rate is by acquiring the Helmholtz resonance frequency in the combustion chamber. This work uses a piezoelectric pressure transducer to obtain the Helmholtz frequency mode of the combustion chamber in a laboratory scale test bench with high-density polyethylene (HDPE) and gaseous oxygen, and is based on the principle that this frequency is inversely proportional to the square-root of the chamber volume. With the chamber volume variation, the port diameter of the grain variation is obtained. In conclusion, the calculated variation of port diameter agreed well with the correlation for average regression rate, determined from mass loss during operation.